The Use of ChatGPT-Based Interactive Exercises to Improve Students’ Vocabulary Mastery - Miftahul Jannah; Mashuri Mashuri; Andi Patmasari; Mochtar Marhum (Journal of General Education and Humanities, 2026)
This study investigates the use of ChatGPT-based interactive exercises to improve eighth-grade students’ vocabulary mastery at SMP Astra Makmur Jaya. The research employed a quantitative, quasi-experimental design with an experimental and a control group. Students’ vocabulary mastery was measured through pre-test and post-test scores, focusing on two aspects: meaning and use. The experimental group received six sessions of ChatGPT-based, collaborative, small-group interactive exercises, while the control group was instructed through traditional textbook-based methods. The results showed that ChatGPT-based interactive exercises significantly improved students’ vocabulary mastery. The experimental group's post-test score improved to 82.32, while the control group's average score was 70.53. Further statistical analysis revealed that the t-counted value (3.92) was higher than the t-table value (2.008), indicating a significant difference between the two groups. These findings indicate that ChatGPT-based interactive exercises effectively improve students’ vocabulary mastery by providing contextual practice, immediate feedback, and increased student engagement. Therefore, the findings indicate that ChatGPT can serve as an effective learning tool to improve students’ vocabulary mastery.